Characterization of the novel HLA‐C*08:159 allele by next‐generation sequencing. (13th March 2019) - He, Yanmin; Wang, Wei; You, Xuan; He, Ji; Faming, Zhu
Abstract : HLA‐C*08:159 differs from HLA‐C*08:02:01:01 by one nucleotide substitution at codon 219 in exon 4.